Impact of selecting the cutting technology on production time and cost - Drndarević Branko; Nedić Petar; Vulović Dušan; Milovanović Aleksandar; Čeković Ivana (Mining and Metallurgy Engineering Bor)
This paper analyzes the technology of cutting processing for supports the mold clamping jaws made of 1C60 material. The number of clamping moves, required to produce the workpiece, is defined, as well as the adoption of necessary cutting tools with appropriate cutting modes on the basis of used material and CNC machine. A detailed analysis is provided for the circumferential milling of pockets with diameters of Ø250 mm and height of 30 mm, Ø200 mm and height of 30 mm, and Ø100 mm and height of 40 mm. This is due to the material volume processed per unit of time, which significantly affects the production time of a workpiece. The impact of selecting the offered circumferential milling operations in the HSMWorks software package on production time and tool life is analyzed, using the 2D Pocket and 2D Adaptive Clearing software options. A comparative analysis of the workpiece production time and cost is provided.